Sentidos e significados da participação da mulher em cargos de alta gestão: em uma instituição financeira - Ferrazza, Maria Clarice de Moraes (2019)
Every worker, which includes the woman who holds high management positions, seeks sense and meaning for their existence. This sense and meaning is what determines its continuity and direction, and that therefore produce as purpose, the search for identity, dignity and quality of life, among others things that promote a purpose beyond itself. The objective of the present study was to analyze the relation between perceptions and meanings of women's participation in senior management positions in a financial institution. This is an exploratory study with a qualitative approach. The data collection technique was based on the narratives of eight women who hold senior management positions in a financial institution with a socio-historical analysis of the relation between their perceptions and meanings. The oral narratives produced by the interviewees allowed access to the processes of construction of the perceptions and meanings, where the dialectic relation between the human beings and the world which they are part of was recognized, highlighting elements of historicity, spatiality and sociability. Then, from the individual analysis of the managers, four (common) meaning cores were identified: woman in a management position: mother wife and housewife; gender bias; training; and motherhood. In this way, it was concluded that women feel satisfied with their situation and are proud of their job position as well as of the institution where they work. They are people who want to make a difference in the corporate world and understand that they can collectively build new meanings through their individual perceptions. However, it is undeniable that although the habits change, the initiatives of the organization researched in relation to gender equality is considered shy, and it is distant from the balance between man and woman.